Let's solve the equation step by step.
Part A: Solve the equation \(5 + x - 12 = x - 7\)
-
Combine like terms on the left side: \[ 5 - 12 + x = x - 7 \] This simplifies to: \[ -7 + x = x - 7 \]
-
Next, subtract \(x\) from both sides: \[ -7 + x - x = x - x - 7 \] This simplifies to: \[ -7 = -7 \]
Since both sides of the equation are equal, it shows that the equation is true for all values of \(x\). Therefore, the solution to the equation \(5 + x - 12 = x - 7\) can be stated as:
Solution: The equation is true for all real numbers \(x\).
Part B: Verify the solution using \(x = -4\), \(x = 0\), and \(x = 5\)
To verify if these values satisfy the equation \(5 + x - 12 = x - 7\), we will substitute each value into the original equation.
-
For \( x = -4 \): \[ 5 + (-4) - 12 \stackrel{?}{=} -4 - 7 \] Calculate the left side: \[ 5 - 4 - 12 = 1 - 12 = -11 \] Calculate the right side: \[ -4 - 7 = -11 \] The left side equals the right side, so \(x = -4\) is a solution.
-
For \( x = 0 \): \[ 5 + 0 - 12 \stackrel{?}{=} 0 - 7 \] Calculate the left side: \[ 5 - 12 = -7 \] Calculate the right side: \[ 0 - 7 = -7 \] The left side equals the right side, so \(x = 0\) is a solution.
-
For \( x = 5 \): \[ 5 + 5 - 12 \stackrel{?}{=} 5 - 7 \] Calculate the left side: \[ 5 + 5 - 12 = 10 - 12 = -2 \] Calculate the right side: \[ 5 - 7 = -2 \] The left side equals the right side, so \(x = 5\) is also a solution.
Summary of Verification:
- For \(x = -4\), both sides equal \(-11\).
- For \(x = 0\), both sides equal \(-7\).
- For \(x = 5\), both sides equal \(-2\).
Conclusion: All tested values \(x = -4\), \(x = 0\), and \(x = 5\) verify that the equation \(5 + x - 12 = x - 7\) holds true, confirming that the equation is valid for all real \(x\).